INFLUENCE OF MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT COMISSÃO NACIONAL ELEIÇÕES (CNE) - Quim, Imelda Maria Fidelia; Nufa, Maria Marcela (PT. Altin Riset Publishing, 2024)
The main aim of this research is to conduct an in-depth study and study of the influence of work motivation and discipline on employee work performance at the Comissão Nacional De Eleições (CNE) Dili Timor–Leste. The sample consisted of 30 employees, with a sampling technique using the accidental method, and a questionnaire was a technique or method for collecting data, with multiple linear regression statistical analysis as an analysis tool rather than a hypothesis test using the T-test. The results of the first hypothesis show that motivation has a positive and significant influence on employee work performance at the Comissão Nacional De Eleições (CNE) Dili Timor – Leste as proven by the output results from SPSS which state that the Tstatistic value of the motivation variable produces a value of 3.962 which is greater than The T table value is 1.679 with a significance level of 0.03, which is smaller than the standard significance of 0.5, thus it can be concluded that the Motivation variable has a quite positive and significant influence on employee performance, meaning that the discipline applied can improve employee performance. The results of the second hypothesis show that work discipline has a positive and significant influence on employee work performance at the Comissão Nacional De Eleições (CNE) Dili Timor – Leste as proven by the output results from SPSS which state that the Tstatistic value of the work Discipline variable produces a value of 3.382 which is more The value of Ttable is 1.679 with a significance level of 0.03, which is smaller than the standard significance of 0.5, thus it can be concluded that the work discipline variable has a quite positive and significant influence on employee performance, meaning that the discipline applied can improve employee performance.